2014
DOI: 10.1016/j.jnca.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

RFID seeking: Finding a lost tag rather than only detecting its missing

Abstract: a b s t r a c tThis paper proposes a novel type of RFID application, i.e., RFID seeking. Several existing types of RFID applications such as monitoring, searching, locating/navigating, are similar with RFID seeking. However, they are either inapplicable or vulnerable for RFID seeking scenarios, in which a user is to find a lost tagged item in a blind spot, or to find a wanted item among a mass of similar ones.In this paper, detailed requirements for RFID seeking are suggested. The first secure RFID seeking pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Xie et al's [41] protocol was later improved by Jeon et al [42] in 2014. Jeon et al's protocol suffers from the reader traceability attack, which was not in the original protocol proposed by Xie et al [41]. It is observed that the lack of context in the protocol between the reader and the tag leads to the replay attacks.…”
Section: Secure Rfid Tag Search Protocolsmentioning
confidence: 99%
“…Xie et al's [41] protocol was later improved by Jeon et al [42] in 2014. Jeon et al's protocol suffers from the reader traceability attack, which was not in the original protocol proposed by Xie et al [41]. It is observed that the lack of context in the protocol between the reader and the tag leads to the replay attacks.…”
Section: Secure Rfid Tag Search Protocolsmentioning
confidence: 99%
“…RFID is definitely witnessing upswing [14]. The four major challenges [9,10,12,14] that industry needs to deal with in regard to RFID adoption are discussed as under.…”
Section: Challenges Related To Rfidmentioning
confidence: 99%
“…In a traditional RFID communication protocol, through a wireless environment, RFID reader queries RFID tags that are attached to objects and delivers their responses to a back‐end server to identify and obtain related information about the object. Beside this classic tag identification scenario, RFID searching, emerged as a new trend in RFID applications, aims to communicate or find out a specific tag among a large group of tags . In this case, the RFID application initially knows the target tag and executes a defined protocol to segregate this tag from the others, for example, this mechanism should be used to check whether an item is nearby.…”
Section: Introductionmentioning
confidence: 99%